European cycle tourism: a tool for sustainable regional rural development - Piket, Pieter; Eijgelaar, Eke; Peeters, Paul (Applied Studies in Agribusiness and Commerce, 2013)
We present an economic impacts model based on direct expenditures for European cycle routes, originally designed in 2009 as part of a study commissioned by the European Parliament. At its request, the study was updated in 2012, including a refined version of our model which takes some limitations of the former model into account. Our main findings are that cycle tourists’ daily spending is comparable to that of other tourists, and that cycle tourism can contribute significantly in particular to rural economies that have not previously enjoyed mainstream tourism development. (European) cycle tourism thus proves to be useful as an (additional) tool for regional rural development. We arrived at a total estimated direct expenditures in Europe of almost €44 billion (€35 billion from day trips and €8.94 billion from overnight trips). We applied the model to the routes of EuroVelo, the European cycle route network which is currently being developed, showing their considerable economic potential of over €7 billion in direct expenditures. Furthermore, cycle tourism has a far lower negative impact on the environment (in terms of carbon dioxide emissions) than other forms of tourism. Cycle tourism is therefore a good example of a low carbon tourism product which could be developed as a major slow travel opportunity across (rural) Europe.